Role of mean platelet volume and platelet/ lymphocyte ratio in assessing the severity of acute respiratory infections in children - Diana Madalina Chiheri; Maria Oana Sasaran; Lorena Elena Melit (Amaltea Medical Publishing House, 2020)
Introduction. Acute respiratory infections are one of the most frequent medical conditions among pediatric patients. Although most evolve favorably, acute respiratory failure is one of the major complications, being the main cause responsible for increased mortality. Different and easy to access parameters, obtained as a result of a simple complete blood count, can be considered as inflammatory biomarkers, that are useful in the diagnosis and prognosis of multiple conditions, including acute respiratory infections. Mean platelet volume and the platelet/lymphocyte ratio are among these biomarkers. Objectives. The purpose of the present study is to investigate the usefulness of the mean platelet volume and the platelet/lymphocyte ratio in distinguishing uncomplicated respiratory infections from those with potential evolution towards acute respiratory failure. Material and methods. We conducted a prospective study on 62 patients aged between 1 month and 10 years, with various respiratory conditions, the diagnose being made based on clinical examination, laboratory findings and chest X-ray. An automated complete blood count was performed for each patient. Results. The study group involved 26 patients with complicated respiratory infections that lead to acute respiratory failure, while the control group consisted of patients with uncomplicated acute respiratory infections (N = 36). Gender, rural/urban backgrounds did not differ significantly between the two groups. Mean platelet volume was significantly decreased in the study group (p = 0.0104), being associated with severe respiratory infections. Similar statistically significant results were obtained by comparing the same parameter in the subgroups of cases with pneumonia and acute bronchiolitis. Increased values of platelet/lymphocyte ratio were also correlated with respiratory tract infections complicated by respiratory failure (p = 0.0445). Conclusions. The results of the current study indicate the usefulness of the mean platelet volume and platelet/lymphocyte ratio as predictive markers for the development of acute respiratory failure in children with respiratory pathologies. However, prospective observational studies on larger groups of patients are needed to obtain adequate, relevant results on a larger population sample.